Effect of postural change on the aerodynamic characteristics during takeoff in ski jumping - Yamamoto, K.; Tsubokura, M.; Baleriola, S.; Onishi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to quantify the aerodynamic characteristics during takeoff using computational fluid dynamics (CFD). The CFD method adopted for this study is based on Large-Eddy Simulation. Body surface data were obtained by 3-D laser scanning of an active ski jumper. A model was generated by dividing the data into A 5 segments with joint mobility. Based on video analysis of the actual takeoff movement at a jumping hill, two sets of motion data were generated (world-class jumper A and less-experienced junior jumper B). The incoming velocity was set to 23.23 m/s. The aerodynamic force, flow velocity, and vortices for each model were compared between models. Comparison of the two models shows that aerodynamic forces acting upon models might be influenced by the airflow condition around the model's back. Expansion of the low air-speed domain of jumper B can be caused by a large trunk angle of attack (Meile et al., 2006). The trunk and upper arm motion might cause the flow structure difference of the wake. Two distinct vortexes generated by the arms produced a downwash flow in the wake of jumper A. It is considered that the positioning of the arms in a very low position strongly influences the flow structure. These results suggested that the vortexes generated by the arms seem to be very important for the aerodynamic lift generation.